INPP5D as a potential therapeutic target against Alzheimer's disease. (1st February 2022) - Lin, Peter Bor‐Chian; Tsai, Andy Po‐Yi; Nho, Kwangsik; Lamb, Bruce T.; Oblak, Adrian L
Abstract: Background: Alzheimer's disease (AD) is a progressive neurodegenerative disorder characterized by cognitive decline, robust microgliosis, neuroinflammation, and neuronal loss. Genome‐wide association studies recently highlighted a prominent role for microglia in late‐onset AD (LOAD). Specifically, inositol polyphosphate‐5‐phosphatase (INPP5D) is selectively expressed in brain microglia and one of its common intronic variants (rs35349669; OR=1.08, 95%CI=1.06‐1.11) has been reported to be associated with increased risk of LOAD. INPP5D is linked to the triggering receptor expressed on myeloid cells 2 (TREM2) signaling, but little is known about the function of INPP5D in microglia and how INPP5D regulates TREM2‐related AD pathogenesis. Therefore, we aim to understand the role of INPP5D in microglia and AD pathology. Methods: We performed differential gene expression analysis to investigate INPP5D expression in LOAD and its association with plaque density using transcriptomic (RNA‐Seq) data from the Accelerating Medicines Partnership for Alzheimer's Disease (AMP‐AD) cohort. We also performed quantitative real‐time PCR, immunoblotting, and immunofluorescence assays to assess INPP5D expression and microglial markers in the 5xFAD amyloid mouse model with INPP5D deficiency. Treatment of fibril amyloid‐beta (fAβ) on immortalized human microglial cell line (IMhu) was assessed to investigate the effect of INPP5D under amyloid pathology. Results: INPP5D gene expression was upregulated in LOAD and positively correlated with amyloid plaque density. Inpp5d expression increased as the disease progressed in the 5xFAD mice, and selectively in plaque‐associated microglia. Also, the protein expression of INPP5D was induced by fAβ treatment in IMhu cells. Inpp5d deficiency mitigated the plaque burdens and neuropathology in the 5xFAD mice and further protected against behavioral deficits induced by amyloid pathology. Conclusions: Our findings show that INPP5D expression increases throughout the AD progression and is predominantly in plaque‐associated microglia. Importantly, inhibited INPP5D expression reduces amyloid pathology, highlighting INPP5D as a potential therapeutic target.